Use of hydrocolloids to control food appearance, flavor, texture, and nutrition - Nussinovitch, A.; Hirashima, Madoka (Wiley, 2023)
"In Use of Hydrocolloids to Control Food Appearance, Flavor, Texture and Nutrition, a team of distinguished food researchers combines comprehensive and authoritative discussions on the conventional use of hydrocolloids to influence shape, structure and organoleptic properties of foods with exciting and emerging areas of innovation, such as texturing for 3D printing and enhancement of food nutrition. The book explores the four principal quality factors of food: appearance, flavor, texture and nutrition, and introduces students and food technologists to the myriad uses of hydrocolloids. It also presents illustrations of relevant commercial food products that rely on hydrocolloids for their appeal, as well as recipes exemplifying the unique abilities of particular hydrocolloids. Readers will also find: *A thorough introduction to the use of hydrocolloids to control food size and shape, including the manipulation of select geometrical properties of foods *A comprehensive exploration of the use of hydrocolloids to modulate food color and gloss, including the psychological impact of those properties *Practical discussions pertaining to the modification of food taste and odor using hydrocolloids *A thorough description of the ways in which hydrocolloids are used to improve crispy, crunchy and crackly foods The book explores the four principal quality factors of food: appearance, flavor, texture and nutrition, and introduces students and food technologists to the myriad uses of hydrocolloids. It also presents illustrations of relevant commercial food products that rely on hydrocolloids for their appeal, as well as recipes exemplifying the unique abilities of particular hydrocolloids"-- Provided by publisher.
Keywords: Food additives.; Food -- Sensory evaluation.; Hydrocolloids -- Industrial applications.; elektronické knihy; electronic books